The Implementation of Health Education Using Snake & Ladders Game and Audiovisual Media to Improve Stunting Knowledge Level on Primigravida Mothers - Anggeriyane, Esme; Rahmatullah, M. Rifqi; Anwari, Muhammad (Gaster, 2024)
Background: Stunting is the condition where a child’s growth and development are disrupted due to chronic malnutrition and recurrent infections, especially in the first 1000 days of life. Increasing the mother's knowledge needs to be carried out with various health education media approaches. Objective: To determine the different effects of health education using the Snakes & ladders game and audiovisual media on the stunting knowledge level of primigravida mothers at Pekauman Community Health Center of Banjarmasin. Method: This research was quasi-experimental with a two-group pretest and posttest design with two kinds of interventions. The population was 67 primigravida mothers, purposive sampling with 60 primigravida mothers who came for antenatal care and bivariate analysis used independent sample T-test. Results: There were differences average score of knowledge before health education using the snake and ladders game was 70.00, and the audiovisual media was 65.57. Then, after health education media using the game of snakes and ladders was 91.77, and audiovisual media was 89.33. Conclusions: Health education using the snakes and ladders game had a higher value and was more effective than audiovisual media in improving the stunting knowledge level of primigravida mothers. Health workers can provide interesting health education about stunting to primigravida mothers.